ASEAN-5 Countries Stock Returns in Light with the Three-Fama and French Factor Model in Global Perspective - Hajanirina Andrianantenaina (JAAF (Journal of Applied Accounting and Finance), 2018)
This paper attempts to investigate the three factor model proposed by Fama and French (1993) upon the five country members within the Association of Southeast Asian Nations or simply ASEAN-5. Most of the studies on these countries deal with the cointegration or co-movement of market stock returns. In overall, these markets are found cointegrated and break the boundaries amongst the cross-border. Besides, global interraction is also studied. Specific factors are not yet considered. Thus, global interaction is studied using the global three factor model. The samplesconsist of five countries global daily stock market index including Indonesia, Malaysia, Philippines, Singapore and Thailand from 2013 to2018. The result of this research shows a positive significant small minus law (SML) factors towards the global index for the case of Phillipines. Yet, other factors do not. Surprisingly, Indonesia, Malaysia, Singapore and Thailand are found insignificant towards the global factors.